Adaptabilidade de carreira e os sintomas de ansiedade em discentes de pós-graduação de uma instituição pública - Coradini, Juciéle Fátima (2021)
Postgraduate studies in Brazil had a growth of 48% in the last decade as informed by the president of CAPES (GOVERNO DO BRASIL, 2021). Students who opt for postgraduate studies report difficulties in developing their skills and difficult placement in the job market. In view of this, it is clear that these obstacles contribute to the increase in mental illness, stress, anxiety and depression were some of the most cited symptoms, it is also highlighted that these students are six times more likely to face anxiety and depression in comparison with the general population (ANPG, 2019). Considering the context presented, the general objective of the study is to analyze the relationship between career adaptability and anxiety symptoms triggered in graduate students. Therefore, we chose to carry out a survey (Survey) with graduate students at the Federal University of Santa Maria, a public institution located in the city of Santa Maria, Rio Grande do Sul. The data collection stage will consist of the application of a survey questionnaire divided into three parts: Sociodemographic Data; Career Adaptability Scale – EAC and; Trait Anxiety Inventory (STAI – T), State Anxiety (STAI-E). Quantitative data were treated with the aid of statistical software and analyzed using descriptive statistics, standardization of scales and structural equation modeling (PLS–SEM). As a result, it was found that approximately 80% of students suffer from symptoms of anxiety, which is a significant incidence. By standardizing the dimensions of the EAC, it was found that the students showed a high level of Concern and Confidence, developing these skills very well. As for IDATE-T, they demonstrated anxiety (43.87%), they are in depression (41.89%), demonstrating that they have this symptom throughout their lives; for the IDATE-E they reported having symptoms of anxiety (55%) and depression (33.43%), one of the symptoms of depression is anxiety. Still, to verify the relationships between the dimensions, a partial structural equation model was proposed, demonstrating that of the eight hypotheses proposed, five were accepted, meaning that there are more negative than positive relationships between anxiety symptoms and the dimensions of career adaptability. The State-Anxiety aspect was negatively related to Control and Curiosity and positively to Worry and Trait Anxiety was negatively related to Control and positively related to Worry. In view of the results, there is a need to raise awareness of prevention and the increase in cases of students with anxiety, considering the damage caused by this disease and the importance of adopting effective strategies to cope with it.